Pyrene-functionalized polymeric carbon nitride with promoted aqueous–organic biphasic photocatalytic CO2 reduction - Gong, Xuezhong (2020)
We have demonstrated a simple copolymerization process to covalently graft pyrene-functional groups on the polymeric carbon nitride (PCN) surface. The resulting pyrene functionalized carbon nitride (Py-PCN) exhibits unique biphasic photocatalytic activities, which enable efficient CO2 photoreduction in aqueous solution with simultaneous alkene (C[double bond, length as m-dash]C) oxidation in the organic phase. The great biphasic activities are attributed to the increased lipophilicity from surface pyrene-functional groups, which allows the hydrophobic alkene molecules to readily approach the PCN surface and react with the hydroxyl radicals created from –OH oxidation by photogenerated holes. In this way, the alkene compounds indirectly consume the photo-holes from excited Py-PCN, promoting the overall photocatalytic process. Our study provides a new strategy for solar fuel production with simultaneous organic synthesis by the oxidation power of photo-holes on amphiphilic metal-free semiconductors.